Bounded rationality as an essential component of the holdup problem - Mathias Erlei; Wiebke Roß (Verein für Socialpolitik, Ausschuss für Wirtschaftssysteme und Institutionenökonomik, 2015)
We provide experimental evidence for the hypothesis that bounded rationality is an important element of the theory of the firm. We implement a simplified version of a mechanism designed to perfectly solve the holdup problem under conditions of perfect rationality (Maskin 2002). We test whether this mechanism is able to perfectly solve our experimental holdup problem or may at least improve economic performance. We find that this is not the case: the implementation of the mechanism worsens economic performance. We reconstruct the main features of participants' behavior by applying the logit agent quantal response equilibrium (McKelvey and Palfrey 1998) as an equilibrium concept that takes players' potential mistakes into account.
Keywords: D23; C92; L23; 330; bounded rationality; transaction costs; incomplete contracts; experiment; mechanism design